ENTEROVIRAL MENINGITIS IN CHILDREN: MODERN APPROACHES TO DIAGNOSIS AND TREATMENT - G. P. Martynova; N. S. Strashnikova; I. A. Kutisheva; A. B. Belkina; A. V. Karasev (LLC "Diagnostics and Vaccines", 2018)
Objective. To reveal the clinical and epidemiological features of еnterovirus meningitis (EVM) in 140 children of Krasnoyarsk in the period of seasonal rise of morbidity in 2017.Materials and methods. For the etiological interpretation of the enterovirus infection (EVI), a molecular biological and virological study of the cerebrospinal fluid, two samples of feces, a swab from the oropharynx, the contents of the vesicles was carried out. Statistical processing of data was carried out using the PASW Statistics 17.0 program.Results. In the Krasnoyarsk Territory, an annual increase in the incidence of EVI is registered, exceeding the average for the country. Serous meningitis is traditionally the main clinical form of EVI. Among the observed patients with EVM, the main group consisted of preschool children (32.9%) and school age (30%), mainly organized in children's groups (84.3%), and the summer-autumn seasonality of the disease remains. Meningitis was observed in 82.8% of patients, meningitis combined with exanthema - in 10%, with herpangina - in 2.1%, with myalgia  - in isolated cases . Mediastinal forms of the disease predominated (96.4% - 135 people), severe forms of the EVM were diagnosed only in 3.6% (5 patients). The clinical picture is traditionally represented by three leading syndromes: intoxication, cerebral and meningeal. The implementation of the epidemic process in 2017 was mainly represented by enteroviruses Coxackie B, B1, B2, B4. Despite the relatively favorable course of the EVM, residual events were in 10% of patients (14 people) at the time of discharge.